OXIDATIVE AND ANTIOXIDANT STATUS IN SMOKING MEN (Iraqi Journal of Medical Sciences, 2016)
Background: Free radicals in cigarette smoke may cause oxidative damage to macromolecules, contributing to cardiovascular diseases and cancer. Decreased plasma antioxidant concentrations in smokers may indicate cigarette smoke–related oxidative stress. Objective: We compared the effects on serum antioxidant concentrations in confirmed active smokers with those in nonsmokers, independent of differences in dietary intakes and other covariates. Methods: Serum samples from 60 smokers, and 40 nonsmokers aged 15-60 years were analyzed for ascorbic acid (vitamin C), ?-tocopherol (vitamin E), and retinol (vitamin A), by using high performance liquid chromatography (HPLC). The measurement of serum lipid profile, and total lipid peroxidation, oxidized HDL (Ox-HDL) was done as well. Results: Showed significantly lower serum antioxidant vitamins (A, C & E) concentrations in smokers more than in nonsmokers. Smokers had significant elevation in serum malondialdehyde (MDA) (p